1999
DOI: 10.1182/blood.v93.4.1413
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M Production and Regulation by Human Polymorphonuclear Neutrophils

Abstract: Oncostatin M (OSM) is an interleukin-6 (IL-6) family cytokine known in particular to induce the synthesis of acute-phase proteins by hepatocytes. Because human polymorphonuclear neutrophils (PMN) can secrete numerous cytokines, the potential production of OSM by PMN was investigated. Highly purified PMN were found to contain an intracellular stock of preformed OSM that was rapidly mobilized by degranulating agents such as phorbol myristate acetate and granulocyte-macrophage colony-stimulating factor (GM-CSF). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(69 citation statements)
references
References 29 publications
3
63
2
1
Order By: Relevance
“…4D,E, inset, arrowheads). Grenier et al (1999, 2001) showed that human blood PMNs were able to release OSM in the inflammatory response. In contrast to PMNs, almost all eosinophils in human are distributed in the mucosal tissues not in the circulation (Weller, 1991; Matthews et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4D,E, inset, arrowheads). Grenier et al (1999, 2001) showed that human blood PMNs were able to release OSM in the inflammatory response. In contrast to PMNs, almost all eosinophils in human are distributed in the mucosal tissues not in the circulation (Weller, 1991; Matthews et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Northern blot analysis revealed that OSM mRNA was expressed at the highest level in the bone marrow, predominantly in thymus, but not in spleen, small intestine, lung, or liver of adult mice (Yoshimura et al, 1996). Although circulating polymorphonuclear neutrophils (PMNs) are shown to produce OSM (Grenier et al, 1999), the localization of OSM mRNA in hematopoietic organs remains unclear. To examine which cells express OSM in the hematopoietic organs during murine embryogenesis and in the adult mice, we used in situ hybridization techniques and immunohistochemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that OSM alone induced the release of GM‐CSF from epithelial cells, suggesting an interaction between these cytokines. Indeed, GM‐CSF has been shown to induce the release of OSM from neutrophils ( Grenier et al ., 1999 ), suggesting that a positive feedback reaction may occur within the context of allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…OSM is produced in cell types that are known to increase in number and activity in asthma, including monocytes and macrophages, activated T cells and neutrophils [17, 30, 31]. More recently, it has also been demonstrated that OSM is produced by dendritic cells [32].…”
Section: Osm Is Produced In Cell Types That Are Up‐regulated N Asthmamentioning
confidence: 99%